Pelatihan Penggunaan Software Aplikasi Penerjemah Bahasa Indonesia - Bahasa Gorontalo bagi Kelompok Guru SD Mata Pelajaran Muatan Lokal (MULOK) di Kecamatan Kota Selatan Kota Gorontalo - Ilham, Jumiati; Dako, Rahmat D.R; Ridwan, Wrastawa (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
he implementation of this activity aims to provide participant with knowledge and skill concerning the use ofandroid-based Indonesia-Gorontalo language translator software (TransGI), which can make it easier for teachers toknow and to increase the vocabulary of Gorontalo. Thus, it is expected that by providing teachers with this training thenwill be able to assist students in using the translator software. The method used is to carry out training activity that beginwith the provision of basic materials about bahasa Gorontalo, subsequent, the application is installed to the smartphonedevice of the teachers participants' and attempt to use the application of TransGI. Training activity is successfullyimplemented by providing understanding, insight and knowledge about bahasa Gorontalo. In addition, the result of thisactivity is expected to further increase student interest and student learni ng outcomes with the help of TransGIapplications